Case Report: Plummer's adenoma in Prader–Willi syndrome - Corica, Domenico; Toscano, Fabio; Moleti, Mariacarla; Pepe, Giorgia; Campenni, Alfredo; Fadda, Guido; Dionigi, Gianlorenzo; Romeo, Carmelo; Aversa, Tommaso; Wasniewska, Malgorzata (Frontiers in Pediatrics, 2024)
Thyroid nodules in children are less common than in adult but they are about two-to three-fold at risk of being malignant compared to adults. Among thyroid nodular diseases, Plummer's adenoma is a very rare occurrence in pediatrics and nowadays there is no literature evidence of this diagnosis in patients with Prader-Willi Syndrome (PWS). We report a case of a 9-year-old caucasian boy affected by PWS presented with a rapidly growing palpable mass in the thyroid lodge associated with subclinical hyperthyroidism. Laboratory and further examinations (thyroid ultrasound, fine needle aspiration of the nodule, scintigraphy) were strongly suggestive for Plummer’s adenoma, so the patient underwent left hemi-thyroidectomy surgery and the anatomo-pathological examination confirmed the diagnosis. Our case describes the first evidence of isolated follicular adenoma in children with PWS. Surgery is the only therapeutic option in younger children. Further evidences are necessary to asses a possible correlation between these two conditions and the existence of potential risk factors